Sustainable dual thrust hybrid rocket motor using polylactic acid as sustainer fuel in multilayered tubular fuel grain - Muhammad Nadzri, Mohamad Mukri Najmi; Mahat, Muhammad Yusuf; Ismail, Izham Izzat; Abdul Kadir, Siti Zafirah; Zazuzila Nadzri, Nur ‘Ain Najlaa; Azami, Muhammad Hanafi (Atlantis Press, 2025)
This study explores the thrust modulation capability of a hybrid rocket motor (HRM) using a novel multilayer tubular (MLT) fuel grain configuration. The fuel design integrates two distinct fuel materials paraffin wax as a booster and polylactic acid (PLA) as a sustainer arranged in concentric layers to achieve a dual-thrust profile. Two configurations (MLT 1 and MLT 2) were fabricated and tested, each varying in booster and sustainer web thickness. Experimental static firing results demonstrated that MLT 2, with a thicker booster layer, achieved superior performance with a higher specific impulse (106.349 s), regression rate (1.638 mm/s), and thrust (71.482 N) compared to MLT 1. Thrusttime profiles confirmed the successful replication of a boost-sustain combustion behavior. The results validate the potential of passive thrust modulation through fuel grain architecture, offering a sustainable and valve-free approach for dualthrust hybrid rocket applications.